2017
DOI: 10.1007/s00371-017-1462-x
|View full text |Cite
|
Sign up to set email alerts
|

3D color homography model for photo-realistic color transfer re-coding

Abstract: Color transfer is an image editing process that naturally transfers the color theme of a source image to a target image. In this paper, we propose a 3D color homography model which approximates photo-realistic color transfer algorithm as a combination of a 3D perspective transform and a mean intensity mapping. A key advantage of our approach is that the re-coded color transfer algorithm is simple and accurate. Our evaluation demonstrates that our 3D color homography model delivers leading color transfer re-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…where H s was a 3 × 3 matrix that transforms colors from the source to match the ones of the reference, and γ r , γ s are inverse gamma correction values. In this work, we extend the matrix H s as a projective transformation with size 4 × 4 (inspired by color homography [19], [20]). By doing this, the model can deal not only with pixels in the core of the color gamut, but also with those values that appear on the border, which are the most affected by gamut mapping and tone mapping.…”
Section: B Color Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…where H s was a 3 × 3 matrix that transforms colors from the source to match the ones of the reference, and γ r , γ s are inverse gamma correction values. In this work, we extend the matrix H s as a projective transformation with size 4 × 4 (inspired by color homography [19], [20]). By doing this, the model can deal not only with pixels in the core of the color gamut, but also with those values that appear on the border, which are the most affected by gamut mapping and tone mapping.…”
Section: B Color Stabilizationmentioning
confidence: 99%
“…Hwang et al [18] suggested to use moving least squares for color transfer, by also incorporating a probabilistic measure to ensure robustness against noise and outliers. Gong et al [19], [20] proposed a color transfer method based on a projective transformation and a mean intensity mapping. All the above mentioned methods are global, although some local approaches also exist.…”
Section: Introductionmentioning
confidence: 99%
“…В ней трехмерное проективное преобразование использовалось для сопоставления цветовых тел различных проекционных аппаратов [41]. Позже этот же подход был применен для фотореалистичного переноса цветовой палитры между изображениями [42]. В обоих случаях речь идет о взаимной калибровке двух изображений, а не о переходе в некоторое эталонное пространство.…”
Section: проективное преобразование трехмерных цветовых координатunclassified
“…In other words, it is possible to apply CS in projectively transformed CSp. Homography of 3-dimensional CSp proposed for the first time presumably in [33], but applied to another problem -photo-realistic colour transfer.…”
Section: Colour Space Projective Transformmentioning
confidence: 99%